THE METHODOLOGICAL SEARCH IN CONTEMPORARY HISTORY OF PHILOSOPHY - A. A. L'vov (Дискурс, 2017)
From the second half of the XX century history of philosophy has appeared in the very center of a number of vivid and vehement discussions of both methodological and disciplinary character. Scholars were primarily focused upon founding approaches to provide their field with the novel piece of knowledge. At the same time, historical studies in philosophy should have been demoted to the level of the sphere for specialists in case they fail to formulate such a research programme. The present paper considers the most illustrious projects in the field of history of philosophy in the past century. It also represents the results of analyses of various methodological approaches to rethinking the essence of historian of philosophy’s craft, considering the latter as the philosopher, investigator, and scholar. We also discuss such significant historical as philosophical approaches as comparativistics, the history of ideas, doxography, that allowed eminent scholars and authors of the XX century to reconsider the value and importance of the history of philosophy as an independent field of investigation.